Correlation Between Malnutrition and Dental Caries in Children - Shakya, Ajay; Shenoy, Ramya; Rao, Ashwini (Journal of Nepal Paediatric Society, 2013)
Introduction: Dental caries and malnutrition is a public health problem, concentrated more among socioeconomically disadvantaged groups. This study aimed to evaluate the correlation between malnutrition and dental caries among 6, 10 and 12 years children in Mangalore. Materials and Methods: Data about oral health status and body mass index of children of age groups 6, 10 and 12 were collected using a cross-sectional design. Anthropometric measurements and oral examinations were carried out. Statistical test was performed to look for categorical associations between BMI categories and dental caries prevalence and to see if any correlation exists between BMI Score and dental caries severity. Results: The Pearson correlation test result suggested children with less BMI score tend to have more caries affected teeth than children with normal BMI. Conclusions: Physicians and dentists treating young children should consider malnutrition as a risk marker for childhood caries. Inclusion of BMI calculation in the standard dental evaluation of any pediatric patient can provide a screen for prevention, timely diagnosis, and treatment of the children suffering from dental caries and malnutrition. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8171 J Nepal Paediatr Soc. 2013; 33(2):99-102